Batas Usia Anak dan Pertanggungjawaban Pidananya Menurut Hukum Pidana Positif dan Hukum Pidana Islam - Imam Muttaqin (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
Children as young generation is a potential successor to the ideals of national struggle. The child is a capital development that will preserve, maintain and develop the existing development results. Therefore, a child needs of protection in order to ensure the growth and development of the physical, mental and social as a harmonious and balanced. Position son in law is a legal subject is determined from the form and system of the child as community groups and classified as not capable or under umur.Kajian about the age limit of children and criminal liability according to positive criminal law and criminal law of Islam is a very interesting phenomenon to be studied, especially during the many phenomena of a child under the age of sitting on the bench of the accused and detained like big criminals only because of trivial matters. The research used in writing this article is to try to explain about the age limit of children and criminal liability according to positive criminal law and criminal law of Islam. The approach used in menyelesaikanya with normative-juridical approach. Under this approach, the limit of the age of the child and criminal responsibility becomes clear that under Islamic law, the age limit of the child is under the age of 15 or 18 years and the child acts can be considered against the law, only the state can affect accountability. So that the unlawful acts by a child can be excused or could be punished, but not the principal punishment, but punishment ta’zir. While the positive law limits the child’s age is the age of 8 but has not reached the age of 18 years and have never been married and all acts children who violate the law can be punished but maximum imprisonment half of the sentence adults, to prison orjail up to 10 years, imprisonment life and the death penalty does not apply to children.